Electrophysiology in a district general hospital. - Prakash, A. (1995)
OBJECTIVE--To investigate the feasibility of performing electrophysiological studies at a district general hospital and to evaluate the importance of such studies in the management of patients with suspected arrhythmias. DESIGN--Retrospective study of patients having had electrophysiological studies during a three year period. SETTING--District general hospital. SUBJECTS--93 patients (50 men, 43 women, mean age 45.9 years) with suspected arrhythmias. RESULTS--The patients were divided into two groups according to symptoms. Group 1 (34 patients) presented with syncope. Group 2 (59 patients) presented with palpitation. All had previously undergone non-invasive investigations. All had had multiple hospital admissions and outpatient attendances. In group 1 nine patients with no documented arrhythmias had inducible ventricular tachycardia and three of six with suspected bradyarrhythmias had ventricular tachycardia. Fourteen patients had suspected ventricular arrhythmias before electrophysiological studies, which were confirmed in all, four receiving automatic implantable cardioverter defibrillators. Electrophysiological studies were used to guide drug treatment in all patients. Group 2 consisted of 32 patients with reentrant supraventricular tachycardia and 15 with ventricular tachycardia; 12 had no documented arrhythmias. In those with supraventricular tachycardia, accessory pathways were identified in all. In 23 patients drug treatment (guided by electrophysiological studies) was successful. In nine, drug treatment guided by electrophysiological studies were ineffective and radiofrequency ablation was successful. In 15 patients with ventricular tachycardia and palpitations, 10 had their drugs changed after electrophysiological studies and their ventricular tachycardia was suppressed. In five patients electrophysiological studies showed that ventricular tachycardia was unsuppressed and they were referred for an operation or implantation of an automatic cardioverter defibrillator. In 12 patients with no documented arrhythmias electrophysiological studies identified significant arrhythmias in six. There were no complications. CONCLUSIONS--Diagnostic electrophysiological studies can safely and effectively be performed in a district general hospital. These studies are especially effective in investigating patients with syncope, and also provide a strategy for future arrhythmia management.